ЗНАЧЕНИЕ ПРОГРАММНЫХ ДОКУМЕНТОВ В ПРОЦЕССЕ ФОРМИРОВАНИЯ И СТАНОВЛЕНИЯ ОСНОВНЫХ ПРИНЦИПОВ МЕТОДОЛОГИИ НАУЧНО-ИССЛЕДОВАТЕЛЬСКОЙ ДЕЯТЕЛЬНОСТИ ПЕРВОЙ ЧЕТВЕРТИ ХХ СТОЛЕТИЯ - И. В. Мазур (International Journal of Innovative Technologies in Social Science, 2020)
The article considers the importance of program documents in the process of formation and establishment of the basic principles of the methodology of research activities of the first quarter of the twentieth century. The study of the features of the collection, recording and systematization of folklore- ethnographic material in this temporary period made it possible to clarify the features and specifics of collecting activities. Based on the study of the analysis principles of collection, records and studies of folklore and ethnographic material. The main methodological principles have been identified and identified, which the foundation of the region is considered as for further research and development of Ukrainian musical folklore of the first quarter of the XX century.